(untitled) (Nordic Journal of African Studies, 2004)
The battle against poverty and environmental protection in Cameroon will be won or lost in the agricultural sector. This is because agriculture plays a prime role in the economy of the country. Although this role in the economy is critical, the current state of agricultural infrastructure does not match with government’s high-sounding policy of promoting agricultural development. From the forgotten story of agricultural shows after 1985, to the closure or near neglect of major agro-pastoral research and technical institutions in the country, the future of agriculture in Cameroon is bleak and raises a lot of questions. Yet, the Ministry of Agriculture is one of the ministries with a lion’s share of the national budget. This paper argues that the fight against poverty and the drive towards food sufficiency by the State remains a fallacy given the collapsing state of agro-pastoral infrastructures in the country. Using case study analysis, from a province whose population is predominantly rural, the paper revisits the state of these infrastructures in the North West Province, and concludes that the change in government policies in the sector can create a negative multiplier effects on the future use of innovations in the country with far reaching consequences on farmer’s productivity and farm outputs. The reversal of this trend, the author notes, requires short and long-term measures that go beyond State action alone.